The application of Tai Chi leisure and health preservation concept in the construction of modern green lifestyle - Wang, Yaqi; Song, Haoyang (The Journal of the International Society of Chinese Health Practices, 2021)
With the acceleration of the pace of life, people have no time to pay attention to other things except work, more and more people have an unhealthy lifestyle, leading to the emergence of some civilization disease and urban disease. In order to better exercise and relieve the pressure of life, Tai Chi is a good way to keep in good health. This paper analyzes the leisure and health concept of Tai Chi, explores its application in building a modern green life style, and uses the wisdom of the ancients to improve the green life quality of modern people.